Pedagogical Strategies Oriented Towards Development of School Learners’ Positive Interpersonal Relations in Inclusive Education - Monkevičienė, Ona (Pedagogika, 2017)
The article analyses a social dimension of inclusive education – interpersonal relations of SEN primary learners with other pupils in the class and pedagogical strategies that target at development of school learners’ positive interpersonal relations. The researchers have distinguished four most important aspects of the social dimension in inclusive education (Koster et al., 2009; De Boer, Pijl, & Minnaert, 2010; Bossaert et al., 2013): a) friendship relations between SEN learners and other schoolchildren in the class (mutual friendship links, subgroups of learners linked by friendship); b) social interaction of SEN school children with peers (joint leisure activities, completion of assignments together, joint participation in activities); c) subjective feelings of SEN learners and their belief that they are accepted by other learners in the class; d) acceptance of SEN learners in the class (social preferences of peers and social support). The researchers also single out and indicate the barriers in building up positive relations of SEN learners with other school learners related with the abovementioned aspects: social isolation, loneliness, social exclusion and bullying. The article sets the following objectives: a) to identify peculiarities of development of SEN learners’ positive relations with other learners; b) to single out pedagogical strategies oriented towards development of positive interpersonal relations of SEN learners with other schoolchildren. The article presents the results of the qualitative research. The following aspects of development of such learners’ positive interpersonal relations are revealed: a) natural acceptance of SEN learners’ otherness seeing transformability of their abilities to communicate and learn; b) inclusion of SEN learners into interpersonal communication based on experience of social similarity and tolerance to the diversity. Such processes are encouraged by the teacher’s belief in transformability of SEN learners’ powers and demonstration of this belief in the classroom. Inclusion of SEN learners into interpersonal communication is enhanced by encouragement of social interactions between SEN children and other class learners in the natural school environment: creation of communication rituals, situations, practices and spaces, initiation of acceptance, mediation and assistance to SEN learners.